STRATEGI EKSPOR PRODUK OLAHAN KELAPA BULAT PT SAMBU GROUP KE MALAYSIA - Deltalita, Descy; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Indonesia, as the world's largest coconut producer, has great potential in the export industry for processed coconut products. PT Sambu Group is one of the main players in exporting processed coconut products to Malaysia. This research is motivated by the importance of implementing the right export strategy to address the challenges of the global market. This research uses a descriptive qualitative approach, with Michael Porter's theory of competitive advantage as the analytical framework. The study focuses on product differentiation strategies, cost efficiency, and distribution strengthening. Data were obtained through literature review and document analysis. The results show that PT Sambu Group has been able to maintain its export competitiveness through product innovation, partnerships with farmers, and compliance with international standards. This strategy has proven effective in expanding its export market to Malaysia and in strengthening the company's position as a major exporter of processed coconut products in the region. Keywords: Export, Processed Round Coconut, Export Strategy, PT Sambu Group Competitive Advantage, Malaysian Market